Status Report: Cardiac Catheterization Project- Belize - Vinall, Maria (MD Conference Express, 2011)
Until last year, there was no modern cardiac diagnostic or interventional facility in Belieze. Efforts have been underway, however, to install a mobile cardiac catheterization laboratory at the national tertiary/public hospital in Belize City.